Multidimensional modelling of quality of experience for mobile web browsing : : doktorski rad - Baraković, Sabina (S. Baraković ; Fakultet elektrotehnike i računarstva, 2014)
ABSTRACT: The increasing use of mobile devices for Web browsing has driven a rising interest among various actors involved in the service provisioning chain in understanding the factors influencing the quality of the end user experience. Research activities stemming from both the fields of human-computer interaction (focusing on user experience, UX) and networking and telecommunications (focusing on Quality of Experience, QoE) have addressed different factors, both aiming for a similar goal - understanding and enhancing the user satisfaction when browsing Web sites. However, the field of modelling QoE in a mobile Web browsing context, as is the focus of this thesis, is rather young and has a number of open research questions that have been limitedly addressed (or in "abstract fashion") by the research community (both QoE and UX). Therefore, this research has been motivated by the challenge to provide a deeper and more comprehensive understanding of the simultaneous influence of multiple factors on QoE and multiple perceivable characteristics of the experience that contribute to its quality, referred to as QoE features/dimensions, in a mobile Web browsing context. Also, we recognized the need to address QoE as a multidimensional concept, and reveal and quantify the relations among multiple influence factors, QoE features/dimensions, and QoE. In this thesis, we present a multidimensional analysis and modelling of QoE in the context of browsing information, thematic, and e-mail portals via smartphones and tablet devices. Results analysis have shown the existence of significant direct impacts of examined factors (Web site design, Web site loading time, and quality of Web site information) on QoE and its considered features/dimensions (perceived usability of Web site, perceived aesthetics of Web site, perceived Web site loading time, and perceived quality of Web site information), as well as strong relations among QoE and addressed QoE features/dimensions in all considered contexts. This enabled us to specify the most important system and contextual factors that impact QoE and corresponding QoE features/dimensions in the context of mobile Web browsing. A core and unique contribution of this thesis are the multidimensional models of QoE and QoE features/dimensions for mobile Web browsing as pertaining to browsing information portals, thematic portals, and e-mail via smartphones and tablet devices, which represent mutual relations of examined QoE influence factors, QoE, and its features/dimensions. They were derived based on data obtained from the systematic experimental user evaluations of developed mobile test Web sites. The proposed multidimensional models, which quantify the aforementioned mutual relations and impacts, are the first ones in this field of research and they contribute to understanding of QoE in mobile Web browsing context, which may consequently lead to more successful management of user satisfaction. Given the successful validation of the proposed models in a real network scenario, we conclude that they can be used for predicting QoE by various interested actors in the service provisioning chain, who may ultimately act in synergic fashion and rely on each other to achieve common benefits. -